Non-invasive mechanical ventilation in severe acute respiratory syndrome in patients hospitalized for COVID-19 - Sara Sabrina Vieira Cirilo; Raniel da Silva Machado; Alexandre da Conceição Santos; Karine Lima Rodrigues; Baldomero Antonio Kato da Silva (Millenium, 2022)
Introduction: Non-Invasive Ventilation is a form of ventilatory support that promotes improvement in several respiratory parameters such as peripheral oxygen saturation, decreased respiratory work, and a significant reduction in the need for intubation and mortality. It is a widely used therapy in the treatment of severe hypoxemia and refractory to oxygen therapy, a clinical condition observed in patients hospitalized for COVID-19.